Some New Results for a Class of Volterra-Fredholm fractional Integrol-Differential Equations under Integral Boundary Value Problems - Sharif, Abdulrahman A.; Hamood, Maha M.; Ghadle, Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this study, we prove the positive solutions to a fractional Volterra-Fredholm integro-differential equation existence and uniqueness. Along with integral boundary conditions, this equation uses Caputo-Hadamard fractional derivatives. Our method of proof makes use of the Schauder fixed point theorem, the Banach contraction principle, upper and lower solution notions, and these concepts. We present an example to demonstrate the utility of our theoretical conclusions.